An Ecological and Historical Perspective on Agricultural Development in Southeast Asia - Hayami, Yūjirō, 1932-2012 1932-2012 (The World Bank, 2000)
reign planters, but prevented alienation of cultivated land from native peasants, to avoid social instability. In Thailand, concessions were granted for private canal building, but the independent kingdom preserved the tradition of giving land to anyone who could open and cultivate it. Relatively homogeneous landowning peasants dominated Thailand's rural sector. As frontiers for new cultivation closed, the plantation system's initial advantage (large-scale development of land and infrastructure) began to be outweighed by its need to monitor hired labor. The peasant system, based on family labor needing no supervision, allowed Thailand's share of the world market in tropical cash crops to grow, as Indonesia and the Philippines lost their traditional comparative advantage. Moreover, land reform in the Philippines made land markets inactive, with resulting distortions in resource allocation and serious underinvestment in agriculture. This paper - a product of Rural Development, Development Research Group - is part of a larger effort in the group to review rural development in Asian countries. The author may be contacted at hayami@sipeb.aoyama.ac.jp